FORMATION OF CONFIGURATIONS OF GALAXIES UNDER THE INFLUENCE OF MASSIVE BLACK HOLES - M. Melibayev (Galaxy International Interdisciplinary Research Journal, 2023)
We consider a possible variant of the formation of regular galaxies with the help of pairs or three of black holes.